PENGARUH MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE AND SHARE (SSCS)TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMA N 1 LAREH SAGO HALABAN - Putri, Ulfa Aulia; Mukhni, Mukhni (Departemen Matematika, 2024)
The purpose of learning mathematics is mathematical problem solving, thus students must have this competence. However, initial assessments at SMA N 1 Lareh Sago Halaban in class XI showed that each component of mathematical problem solving was remained below grade. One endeavour used the SSCS learning methodology. This study examines how the SSCS model improves students' mathematical problem-solving skills and if it outperforms the direct learning model. This study used quasi-experimental methods. A posttest-only non-equivalent group design was utilised in this investigation, with a significance threshold of α = 0.05 Simple random sampling was used. Research findings were t-tested. SMA N 1 Lareh Sago Halaban students taught utilising the SSCS technique have better mathematical problem-solving skills than those taught directly.Keywords– Mathematical Problem Solving Ability, SSCS, Direct Learning.